Discovery of a disjunct Iberian population and revision of the distribution of the Western Mediterranean endemic Carex olbiensis (Cyperaceae) - Luceño, Modesto; de la Peña, Begoña Quirós; Sánchez-Villegas, Rogelio; Sánchez-Villegas, Manuel; Rodríguez, Fernando Estévez; Martín-Bravo, Santiago (Mediterranean Botany, 2022)
In this paper we report the presence of Carex olbiensis (Cyperaceae) in the CW Iberian Peninsula (Sierra de Gredos, Extremadura region), which represents an important disjunction in relation to the known range of the species and its westernmost new limit. We revised the distribution of this species, which resulted in the likely exclusion of the species from the floras of Bosnia-Herzegovina and Morocco. Finally, we provide an illustration of the species and discuss some aspects of its ecology, morphology, and conservation status.